Genotypic Variability in Salinity Tolerance of Maize Pipe Line Hybrids at Seedling Stage - Maiti, Ratikanta; Rodríguez, Humberto González; Rajkumar, D.; Koushik, Sanjay; Vidyasagar, P. (International Journal of Bio-resource and Stress Management, 2023)
In this study using a simple and novel semi-hydroponic technique, 14 maize pipe line hybrids with high yield potentials were evaluated for salinity tolerance at different levels of stress [control, 0.15 (EC=13.6 dSm-1), 0.2 MNaCl (EC=18 dSm-1)] at seedling stage. This technique is proved to be highly effective and consistent to distinguish genotypes for salinity tolerance. Increasing salinity decreases emergence percentage, shoot and root length and number of adventitious roots in susceptible lines, on the contrary the tolerant lines showed increased number of lateral roots with increasing salinity as a function of osmotic adjustment. Two genotypes have even at 0.2 M NaCl showed high emergence percentage starting from 70% to 77% emergence and more number of adventitious roots, viz. revealing these genotypes have high salinity tolerance. Seven genotypes have at 0.15 M NaCl showed highest emergence starting from 70% to 96.7%. The results revealed that seedling emergence and number of adventitious roots may be considered as selection criteria for salinity tolerance in maize. These genotypes have great potential under saline prone areas.